Elitism in Higher Education and Inequality: Why Are the Nordic Countries So Special? - Elise S. Brezis (Intereconomics, 2018)
Countries in which there are two channels of education may have a separating equilibrium in which individuals with high abilities learn in elite universities and individuals with low ability learn in standard ones. Elite universities have higher budgets, better scholars, better labs and a better student network, resulting in the human capital of these students having a higher productivity in the more competitive tradable sector.
Keywords: 330